One-Step Fabrication of Electrospun Photo-Cross-Linkable Polymer Nanofibers Incorporating Multiwall Carbon Nanotubes and Enzyme for Biosensing. Issue 10 (1st January 2015) - Sapountzi, Eleni; Braiek, Mohamed; Farre, Carole; Arab, Madjid; Chateaux, Jean-François; Jaffrezic-Renault, Nicole; Lagarde, Florence
Abstract : Herein, we report the easy and rapid fabrication of water-stable electrospun nanofibers from blends of the photochemically cross-linkable polyvinyl alcohol styrylpyridinium polymer (PVA-SbQ), carboxylated multiwall carbon nanotubes (MWCNT-COOHs) and glucose oxidase (GOx) for electrochemical biosensor application. Different electrospinning parameters including flow rate, applied voltage, distance between tip and collector, polymer concentration and MWCNT-COOHs content in the electrospun solution were tailored to produce PVA-SbQ/MWCNT-COOH nanofibers with minimal beading and enhanced electrical properties. Optimal PVA-SbQ and MWCNT-COOHs concentrations were 6.7 wt% and 5 wt% with respect to the total solution and polymer mass, respectively. The nanofibers were rendered water insoluble via exposure to UV irradiation for 10 min. The electrochemical properties of electrospun PVA-SbQ/MWCNT-COOH nanofibrous mats were characterized by cyclic voltammetry and electrochemical impedance spectroscopy. Scanning electron microscopy and transmission electron microscopy were used to characterize the morphology of the nanofibers. GOx, used as model enzyme, was further incorporated into the PVA-SbQ/MWCNT-COOH mixture before electrospinning. The obtained biosensor enabled successful detection of glucose by cyclic voltammetry. The resulting novel glucose biosensor revealed very good storage and operational stabilities, a low limit of detection (2 μM) and a wide linear range (up to at least 4 mM).